Labor Supply and Optimization Frictions: Evidence from the Danish Student Labor Market - Jakob Egholt Søgaard (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
Using Danish administrative data, I investigate the magnitude and nature of optimization frictions in the labor market of Danish students. Danish students face a unique institutional setting that makes it possible to distinguish between different types of frictions and estimate their effect on individual utility. I find that frictions significantly affect observed labor market outcomes. In particular, the empirical evidence points to inattention as the dominant type of friction. In contrast, my findings appear inconsistent with real adjustment costs, price misperception and gradual learning. Overall, optimization frictions reduce the utility of individuals by approximately 2-3 percent of disposable income.
Keywords: H21; H24; J22; 330; Optimization frictions; labor supply; bunching; inattention; student labor markets